Socioeconomic Status and Prognosis of Patients With ST-Elevation Myocardial Infarction Managed by the Emergency-Intervention “Codi IAM” Network - Tizón-Marcos, Helena; Vaquerizo, Beatriz; Ferré, Josepa Mauri; Farré, Núria; Lidón, Rosa-Maria; Garcia-Picart, Joan; Regueiro, Ander; Ariza, Albert; Carrillo, Xavier; Duran, Xavier; Poirier, Paul; Cladellas, Mercè; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Despite STEMI emergency intervention networks have spread, inequalities in health care access still have a negative impact on cardiovascular prognosis. The Family Income Ratio of Barcelona (FIRB) is a socio-economic status (SES) indicator annually calculated. Our aim was to evaluate whether SES had an effect on mortality and complications in patients managed by the “Codi IAM” network in Barcelona. Methods: Cohort study with 3,322 consecutive STEMI patients treated in Barcelona from 2010 to 2016.Collected data include treatment delays, clinical and risk factor characteristics, and SES. Patients were assigned to three SES groups according to FIRB score. Logistic regression analysis was used to estimate the adjusted effect of SES on 30-day mortality, 30-day composite cardiovascular endpoint, and one-year mortality. Results: Mean age of patients was 65±13% years,25% were women and 21% had diabetes mellitus. Patients with low SES were younger, more often hypertensive, diabetics, dyslipidemic (p<0.003), had longer reperfusion delays (p<0.03) and treated with bare-metal stents (p<0.03) compared to participants with higher SES. Low SES was not independently associated to 30-day mortality (OR:0.95,95%CI:0.7-1.3),30-day cardiovascular composite endpoint (OR:1.03, 95%CI:0.84-1.26) or one-year all-cause mortality (HR:1.09, 95%CI:0.76-1.56). Conclusions:Although low SES STEMI patients in Barcelona city were younger,had worse clinical profiles and longer revascularization delays, their 30-day and one-year outcomes were comparable to higher SES patients.